Agglomeration Externalities in Germany - Eckhardt Bode (European Regional Science Association (ERSA), 2004)
Several recent econometric investigations found externalities related to the density of economic activity to account for one fifth to one half of total regional variations in average labor productivity in the U.S. and big European countries, including Germany. The present paper shows for German NUTS 3 regions, first, that this result is not robust against a more extensive control for private returns that may be correlated with economic density. The paper presents, second, evidence of various types of agglomeration economies, including labor-market pooling, human-capital externalities, localized R&D spillovers, gains from the variety of intermediate goods, to affect regional productivity significantly. Although the productivity effects of these externalities within regions cannot be identified because they are observationally equivalent to individual returns, they can be identified by exploiting the spatial dimension of the data. Keywords: productivity, agglomeration externalities, spatial econometrics JEL: C21, R12
Keywords: C21; R12; 330; productivity; agglomeration externalities; spatial econometrics